Analisis Hadis Larangan Minum Berdiri Dalam Kesehatan - Amelia Nursyifa; Dinda Ayu Ramadhani Putri; Maulidia Khairada Amalia (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
Islam is the most perfect religion and has regulated many aspects of the lives of its creatures, one of which is correct drinking etiquette. Rasulullah saw. has set an example of drinking ethics for the benefit of his people by prohibiting drinking while standing. Medical experts also support this. Drinking while sitting makes food enter slowly so that the intestinal absorption function will run optimally. There are many hadith that mention the prohibition of drinking while standing, which is attempted to relate it to health. This research is qualitative in nature and uses research methods based on library research by collecting research data sources from various relevant literature sources. Many literature states that drinking while sitting is considered better than drinking while standing. This certainly supports the hadiths which state the prohibition on drinking while standing. Some of the effects of drinking while standing on the digestive system include kidney dysfunction, dehydration, indigestion, pressing on the nerves, causing gerd, and triggering arthritis.